Environmental impacts due to river sand mining: A case study - Piyadasa, Ranjana U. K. (University of Colombo, 2010)
Sand is an essential element of construction and has direct and indirect impacts on a country’s development processes. The sustainable use of sand resources is important to maintain natural ecosystems and support overall development. Sri Lanka’s construction industry which contributes over 8% to the country’s GDP requires over 7 million cubic meters of sand annually (expanded in the short term due to additional demands of post tsunami construction) which is obtained from the country’s river beds, river banks or mined from previous riverbeds and sand dunes. Although until recently manual harvesting was the norm, increasing mechanized and often illegal river sand harvesting has caused a major loss of water security and ecosystem damage due to the lowering of water tables, bank erosion, land degradation and salinity intrusion, damage to infrastructure, and increased health hazards. The present research study was conducted to identify the behavior of environmental impacts due to river sand mining in the Nilwala river. Overmining of the Nilwala River causes many problems like salinization of Matara drinking water due to the intrusion of sea water into the river, collapse of river banks, and loss of river land. The study was focused mainly on groundwater quality changes due to sand mining in the Nilwala river basin area. Wells dug in the right bank of the Nilwala river basin were selected to identify groundwater quality changes due to sand mining in the river. The GIS package Arc View was used to identify the water quality changes in the river and as well as in the flood plain area.